2014
DOI: 10.1021/jf500666w
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release Properties of Zein–Fatty Acid Blend Films for Multiple Bioactive Compounds

Abstract: To develop edible films having controlled release properties for multiple bioactive compounds, hydrophobicity and morphology of zein films were modified by blending zein with oleic (C 18:1 )Δ 9 , linoleic (C 18:2 )Δ 9,12 , or lauric (C 12 ) acids in the presence of lecithin. The blend zein films showed 2−8.5-and 1.6−2.9-fold lower initial release rates for the model active compounds, lysozyme (LYS) and (+)-catechin (CAT), than the zein control films, respectively. The change of fatty acid chain length affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Recently, the potential of zein as an active ingredient for direct compressed tablets and film-based delivery carriers has been investigated in detail [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Moreover, zein was considered a promising film coating material for novel biomedical applications such as medical devices [92][93][94], nanoparticles [95], quantum dot and nanofiber [96,97].…”
Section: Drug Delivery and Biomedical Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the potential of zein as an active ingredient for direct compressed tablets and film-based delivery carriers has been investigated in detail [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Moreover, zein was considered a promising film coating material for novel biomedical applications such as medical devices [92][93][94], nanoparticles [95], quantum dot and nanofiber [96,97].…”
Section: Drug Delivery and Biomedical Applicationmentioning
confidence: 99%
“…Numerous studies have revealed that zein film itself could function as a controlled release matrix for the delivery of active components, such as salicylic acid [80], acetyl salicylic acid [80], iodine [81], nisin [83,84], lysozyme [82,[84][85][86][87], EDTA [82,84], thymol [90,91], catechin [85,87,89], gallate ester [88] and gallic acid [89]. Although these zein films may have different usages, the controlled release profiles of active components are the focus of attention.…”
Section: Zein Film As Delivery Carriermentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these uses are based on the release of active substances that have been added to a zein film . These substances include salicylic acid or acetylsalicylic acid , lysozyme or catechin , nisin , phenolic compounds such as thymol, carvacrol or eugenol .…”
Section: Introductionmentioning
confidence: 99%